Clinical tools to assess balance in children and adults with cerebral palsy: a systematic review. (16th May 2013) - Saether, Rannei; Helbostad, Jorunn L; Riphagen, Ingrid I; Vik, Torstein
<x xml:space="preserve">Abstract</x> We aimed to review tools used to assess balance in clinical practice in children and adults with cerebral palsy (CP), to describe their content and measurement properties and to evaluate the quality of the studies that have examined these properties. CINAHL, Embase, and PubMed/MEDLINE were searched. The COnsensus‐based Standards for selection of health Measurement INstruments (COSMIN) was used to assess the 'quality of studies' and the Terwee criteria were used to assess the 'result of studies'. Twenty‐two clinical balance tools were identified from 35 papers. The content and focus of the tools varied significantly. There was moderate or limited levels of evidence for most of the measurement properties of the tools; the strongest level of evidence was found for the Trunk Control Measurement Scale and the Level of Sitting Scale, in the category 'maintain balance', the Timed Up and Go and the Segmental Assessment of Trunk Control in the categories 'achieve balance' and 'restore balance' respectively. Information on responsiveness was scarce. Further studies providing better evidence for reliability and responsiveness for clinical balance tools are needed. In the meantime, results of studies evaluating effects of treatment of balance in individuals with CP should be interpreted with caution.